Lupus Nephritis Presenting with Mixed Nephrotic and Nephritic Syndrome : A Case Report - I Dewa Ayu Meyta Putri Sandradevi; Nyoman Sutarka (Eduvest - Journal of Universal Studies, 2026)
Lupus nephritis (LN) is a severe manifestation of Systemic Lupus Erythematosus (SLE) that may present with mixed nephritic and nephrotic features. Diagnosis can be challenging when renal biopsy is not immediately feasible. Case Presentation: An 18-year-old female presented with dyspnea, pleuritic chest pain, generalized edema, and recurrent seizures. She exhibited persistent nephrotic-range proteinuria, active urinary sediment, severe hypoalbuminemia, hypocomplementemia, and strongly positive antinuclear antibodies, while anti–double-stranded DNA antibodies were negative. Imaging revealed bilateral pleural effusions and increased renal parenchymal echogenicity. Based on the 2019 EULAR/ACR criteria, she fulfilled 14 points, supporting a diagnosis of SLE. The clinical and laboratory findings were consistent with probable lupus nephritis presenting as mixed nephritic and nephrotic syndrome. She was treated with corticosteroids, mycophenolate mofetil, hydroxychloroquine, antihypertensive agents, electrolyte correction, and supportive therapy, resulting in clinical stabilization during hospitalization. This case illustrates the diagnostic complexity of lupus nephritis in a young female presenting with overlapping nephritic and nephrotic features when renal biopsy cannot be performed immediately. The presence of persistent nephrotic-range proteinuria, active urinary sediment, hypocomplementemia, high-titer ANA, and systemic manifestations fulfilled the 2019 EULAR/ACR classification criteria for SLE, supporting a clinical diagnosis of probable lupus nephritis. In accordance with current guidelines, early initiation of immunosuppressive therapy was justified to prevent irreversible renal damage. This case underscores the importance of integrating clinical, serologic, and laboratory findings for timely decision-making and highlights the need for close follow-up and renal biopsy once clinically feasible to optimize long-term outcomes.